The effect of structural-kinetic features of hologram formation on holographic properties of photopolymers - Smirnova, T.; Sakhno, O.; Lozenko, S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
A thermodynamic model of the holographic recording process in photopolymers have been developed. By the example of photopolymerizing compositions PPC-488 containing oligoetheracrylates and neutral components (NC) we have explored dependencies of holographic characteristics of medium on NC concentration and thermodynamic properties of polymer-NC system. The thermodynamic affinity of the polymer forming during recording and NC was evaluated using the difference of their solubility parameters ∆δP,NC. We have determined the feasible range of variation for ∆δP,NC and optimal concentration of NC ( 0 opt N ) that ensure high-performance recording. It was ascertained that excess in NC concentration over the optimal value leads to the increase of photoinduced light scattering in the layer. The efficiency of scattering depends on the size of microphase enriched by NC. We have determined the size of microphase particles and its dependence on kinetic parameters of polymerization.